ANALISIS PERTIMBANGAN HUKUM HAKIM PUTUSAN NOMOR 640/Pdt.G/2019/PN Dps - NIM. A1011211009, KHARISMANTO (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Decision Number 640/Pdt.G/2019/PN Dps is a case of breach of contract in a lease agreement between PT. Dayton Borneo Sukses as the plaintiff and PT. Mulia Bhakti Kahuripan as the defendant, where the plaintiff's claim for the Minimum Charge was rejected by the judge because it did not comply with the contents of the agreement and the proven facts, even though the judge ordered the return of heavy equipment that was not listed in the petitum. This prompted the plaintiff to take legal action up to cassation, which was then granted by the Supreme Court based on the principle of justice. This study aims to analyze the legal considerations in the decision and examine the legal consequences for the parties using the normative legal method through a case and statutory approach. The results show that the judge's considerations at the first level emphasize the principles of legal certainty and benefit, while the cassation decision confirms the recognition of the plaintiff's rights as final and binding. The defendant is required to implement the contents of the decision, and if not complied with, he can be subject to coercive measures. This decision reflects the importance of implementing the principles of justice and legal certainty in civil disputes. Keynotes : Lease Agreement, Default, Judge's Legal Considerations Abstrak Putusan Nomor 640/Pdt.G/2019/PN Dps merupakan perkara wanprestasi dalam perjanjian sewa menyewa antara PT. Dayton Borneo Sukses selaku penggugat dan PT. Mulia Bhakti Kahuripan sebagai tergugat, di mana tuntutan penggugat atas Minimum Charge ditolak oleh hakim karena tidak sesuai dengan isi perjanjian dan fakta yang terbukti, meskipun hakim memerintahkan pengembalian alat berat yang tidak tercantum dalam petitum. Hal ini mendorong penggugat menempuh upaya hukum hingga kasasi, yang kemudian dikabulkan oleh Mahkamah Agung berdasarkan asas keadilan. Penelitian ini bertujuan menganalisis pertimbangan hukum dalam putusan tersebut serta menelaah akibat hukum bagi para pihak dengan menggunakan metode yuridis normatif melalui pendekatan kasus dan perundang-undangan. Hasilnya menunjukkan bahwa pertimbangan hakim pada tingkat pertama lebih menekankan asas kepastian dan kemanfaatan hukum, sementara putusan kasasi menegaskan pengakuan atas hak penggugat secara final dan mengikat. Tergugat diwajibkan melaksanakan isi putusan, dan jika tidak dipatuhi dapat dikenai upaya paksa. Putusan ini mencerminkan pentingnya penerapan asas keadilan dan kepastian hukum dalam sengketa perdata. Kata Kunci : Perjanjian Sewa-Menyewa, Wanprestasi, Pertimbangan Hukum Hakim